Recent advances in polysaccharides stabilized emulsions for encapsulation and delivery of bioactive food ingredients: A review. (15th August 2020) - Zhang, Ruyuan; Belwal, Tarun; Li, Li; Lin, Xingyu; Xu, Yanqun; Luo, Zisheng
Highlights: The most common polysaccharides stabilized emulsions are comprehensively summarized. The relationship between polysaccharide structure and emulsifying capacity is discussed. Interaction mechanisms of polysaccharides with other biopolymers are elaborated. In vitro and in vivo models for bioavailability of protected bioactives are reviewed. Future trends of polysaccharides stabilized emulsions are discussed. Abstract: Many bioactive food ingredients were encapsulated in different forms to improve their stability and bioavailability. Emulsions have showed excellent properties in encapsulation, controlled release, and targeted delivery of bioactives. Polysaccharides are widely available and have different structures with different advantages including non-toxic, easily digested, biocompatible and can keep stable over a wide range of pH and temperatures. In this review, the most common polysaccharides and polysaccharide based complexes as emulsifiers to stabilize emulsions in recent ten years are described. The close relationships between the types and structures of polysaccharides and their emulsifying capacities are discussed. In addition, the absorption and bioavailability of bioactive food components loaded in polysaccharide stabilized emulsions are summarized. The main goal of the review is to emphasize the important roles of polysaccharides in stabilizing emulsions. Moreover, speculations regarded to some issues for the further exploration and possible onward developments of polysaccharides stabilized emulsions are also discussed.